2001
DOI: 10.1046/j.1365-2036.2001.00992.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and relapse of bleeding from duodenal ulcer: respective roles of acid secretion and Helicobacter pylori infection

Abstract: BACKGROUNDHelicobacter pylori infection and gastric acid hypersecretion together with NSAID consumption, are the main factors involved in gastroduodenal injury and bleeding. 1 Peptic ulcer is the most common cause of non-variceal upper gastrointestinal bleeding, accounting for 50±60% of cases. Bleeding episodes are frequent in duodenal ulcer patients, with a prevalence of 15±20% and a mortality up to 7%. 2 Patients who have bled once are considered to be at a higher risk of re-bleeding. Of duodenal ulcer patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 30 publications
1
5
0
2
Order By: Relevance
“…In the present study, recurrence of bleeding was demonstrated in only two of 422 patients after H. pylori eradication, giving a rebleeding incidence as low as 0.22% per patient‐year of follow up, which argues against the necessity of prescribing maintenance antisecretory therapy in these cases. This figure is in agreement with that previously reported in the literature (Table 1) [17–46]. As the follow‐up time markedly varied among studies, the risk of rebleeding is better expressed as “yearly” recurrence of bleeding.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, recurrence of bleeding was demonstrated in only two of 422 patients after H. pylori eradication, giving a rebleeding incidence as low as 0.22% per patient‐year of follow up, which argues against the necessity of prescribing maintenance antisecretory therapy in these cases. This figure is in agreement with that previously reported in the literature (Table 1) [17–46]. As the follow‐up time markedly varied among studies, the risk of rebleeding is better expressed as “yearly” recurrence of bleeding.…”
Section: Discussionsupporting
confidence: 92%
“…As the follow‐up time markedly varied among studies, the risk of rebleeding is better expressed as “yearly” recurrence of bleeding. Thus, mean incidence of peptic ulcer rebleeding calculated from studies where H. pylori was eradicated and no maintenance antisecretory therapy was prescribed was only per patient‐year of follow up (Table 1) [17–46].…”
Section: Discussionmentioning
confidence: 99%
“…Adamek, 1994 151 Re-bleeding not evaluated Altorjay, 2000 152 Re-bleeding not evaluated Less than 6 months' follow-up Amendola, 1999 153 No control group (all patients received H. pylori eradication therapy) Arkkila, 2001 154 Insufficient data (no response from the authors) Capurso, 2001 155 No previous UGI bleeding No control group (all patients received H. pylori eradication therapy) Chan, 1997 156 All patients received NSAIDs Chan, 1998 157 Re-bleeding not evaluated Chan, 2001 158 All patients received NSAIDs Chan, 2002 159 All patients received NSAIDs Chan, 2002 160 All patients received NSAIDs No previous UGI bleeding in one group Chen, 1996 161 No control group (all patients received H. pylori eradication therapy) Less than 6 months' follow-up Chen, 1998 162 No control group (all patients received H. pylori eradication therapy) Less than 6 months' follow-up Di Mario, 1997 163 No control group (all patients received H. pylori eradication therapy) Fakhreih, 1995 164 No control group (all patients received H. pylori eradication therapy) Gisbert, 1995 165 No control group [all patients (one) received H. pylori eradication therapy] Gisbert, 1999 166 No control group (all patients received H. pylori eradication therapy) Hsieh, 2001 167 Re-bleeding not evaluated Huelin Benitez, 1998 168 No control group (all patients received H. pylori eradication therapy) Jaspersen, 1994 169 No control group (all patients received H. pylori eradication therapy) Jaspersen, 1994 170 No control group (all patients received H. pylori eradication therapy) Less than 6 months' follow-up Jaspersen, 1995 171 No control group (all patients received H. pylori eradication therapy) Krizman, 1997 172 No control group (all patients received H. pylori eradication therapy) Kung, 1997 173 No control group (all patients received H. pylori eradication therapy) Less than 6 months' follow-up Labenz, 1994 174 No control group (all patients received H. pylori eradication therapy) Lai, 1998 175 No control group (all patients received H. pylori eradication therapy) Lai, 2000 176 Re-bleeding not evaluated Lee, 1998 177 Re-bleeding not evaluated…”
Section: Reason For Exclusionmentioning
confidence: 99%
“…However, duodenal ulcer recurrence with bleeding may occasionally occur in patients cured of H. pylori, even if acid output is normal 45 . Kang et al 44 found that patients with bleeding peptic ulcer had a higher proportion history of peptic ulcer disease.…”
Section: Discussionmentioning
confidence: 99%